(untitled) (Canadian Journal of Counselling and Psychotherapy, 2020)
Little is known about how factors related to the post-secondary academic setting impact Canadian students’ self-reported anxiety. Using a socio-ecological framework, we examined lifetime prevalence and correlates of self-reported student anxiety. Data were collected from 593 university students (422 of whom were undergraduates) from a university in central Canada through an online survey. Descriptive statistics and a series of regression models were used to examine the study’s objectives. Most students reported having experienced anxiety that had impacted their lives. Findings provide support for a socio-ecological explanation of anxiety: socio-demographic, relationship, and academic factors predicted self-reported student anxiety. The results highlight the need to ensure that campus services and supports are well equipped to address the mental health problems of students. Theoretical, practice, and research implications are noted.